The Concept of Death Penalty in a Pancasila State (Perspective of Official Religion in Indonesia) - Muryani, Maria Anna; Rosyida, Noor (Universitas Islam Negeri Walisongo Semarang, 2020)
The death penalty concept in perspective the official religion in Indonesia is an issue that is worthy of study in line wiht the execution of drug convicts lately. MUI fatwa No.10/Munas VII/MUI/ 14/2005 on the death penalty in a Specific Crime allow the penalty in certain types of criminal acts. In a latter sent to his congregation, paul chapter 13 yat 1-4 mention about the goverment’s authority to impose penalties for offenders. St. Agustine and Thomas Aquinas assume that the state, in order to achieve common prosperity, can performthe death penalty. St. Agustine assess the death penalty as a way to prevent crime and protect those who are innocent. Buton the other hand the human right activists who joined in contrast, Impartial and Elsam reject the death penalty and the Roman catholic Church and Christians argue that the death penalty should not be carried out because it violates basic human right, namely the righ to life. Therefore, research is the theme of the death penalty in the perspective of the official state religions in the frame Pancasila want to investigate this further on the death penalty in the perspective of religion are officially recognized by the state as defined in the following issues; How does the concept of the death penalty in perspective official religions in Indonesia are contained in their holy book? And How the concept of the death penalty to be reviewed from the perspective of the state ideology Pancasila? This research is a normative juridical or doctrinal research. This study uses several approaches that approach to the concept (conceptual approach), approach to the comparative (comparative approach) and approach to legislation (statute approach). This study was a descriptive analytical method of data collection in the form of a data library (library research) and interviews.[]Konsep hukuman mati dalam perspektif agama resmi di Indonesia merupakan sebuah isu yang patut dikaji sejalan dengan pelaksanaan eksekusi mati narapidana narkoba. Fatwa MUI No.10/Munas VII/MUI/14/2005 tentang pidana mati dalam Tindak Pidana Tertentu memungkinkan adanya pidana dalam jenis tindak pidana tertentu. Dalam surat terakhir yang dikirim ke jemaahnya, pasal 13 ayat 1-4 menyebutkan tentang kewenangan pemerintah untuk menjatuhkan sanksi bagi pelanggar. St Agustine dan Thomas Aquinas beranggapan bahwa negara, untuk mencapai kesejahteraan bersama, dapat melaksanakan hukuman mati. St Agustine menilai hukuman mati sebagai cara untuk mencegah kejahatan dan melindungi mereka yang tidak bersalah. Namun di sisi lain para aktivis HAM yang bergabung sebaliknya, Imparsial dan Elsam menolak hukuman mati dan Gereja Katolik Roma dan Kristen berpendapat bahwa hukuman mati tidak boleh dilakukan karena melanggar hak asasi manusia, yaitu hak untuk hidup. Oleh karena itu, penelitian yang mengangkat tema pidana mati dalam perspektif agama resmi negara dalam bingkai Pancasila ingin diteliti lebih jauh mengenai hukuman mati dalam perspektif agama yang diakui secara resmi oleh negara sebagaimana dirumuskan dalam isu-isu berikut; Bagaimana konsep hukuman mati dalam perspektif agama-agama resmi di Indonesia yang dimuat dalam kitab sucinya? Dan Bagaimana konsep hukuman mati ditinjau dari perspektif ideologi negara Pancasila? Penelitian ini merupakan penelitian yuridis normatif atau penelitian doktrinal. Penelitian ini menggunakan beberapa pendekatan yaitu pendekatan konsep (conceptual approach), pendekatan komparatif (comparative approach) dan pendekatan perundang-undangan (statute approach). Penelitian ini merupakan metode pengumpulan data deskriptif analitik berupa pustaka data (studi pustaka) dan wawancara.